COVID and the South African Family: Cyril Ramaphosa, President or father?. (December 2021) - Hunt, Sally
Abstract: World leaders had to guide their people through difficult times in 2020, with many trying to win compliance and support via a range of channels of communication. Cyril Ramaphosa, President of South Africa, faced the same challenge. This study explores the linguistic features of his 14 COVID-related speeches in 2020, with the aim of revealing the world he constructs in them and how he furthers his political aims. A blend of corpus linguistics and critical discourse analysis is used to draw out frequent patterns of representation within the generic structure which emerged from the data. The metaphorical construction of the nation as a family, evident in lexical choices, especially we, family and together, creates a relationship of unity between President Ramaphosa and the citizens. His reference to the national addresses as 'family meetings' further flattens the hierarchy implied in the political relationship of governor and governed. These features have the effect of locating the speeches in a time when mediatisation was less pervasive, and in a more personal context. Simultaneously, trust and compliance are invoked by the shift in role as President from a powerful position of control, to a position of shared concern and responsibility.